Women Leadership as Head of State in Contemporary Muslim Thoughts: A Critical Analysis - Rafiq, Saima; Shams-ur-Rehman, Dr. Ghulam Shams-ur-Rehman (Al-Irfan, 2023)
Abstract: - This article is aimed at exploring and discussing the female leadership in Islam and its comparison with the political status of women in the contemporary Muslim thought. The matter of women as head of state has been the subject of repeated controversy. Concerns are often raised about the political empowerment of women in Islamic society. It is evident that Islamic society is dichotomized into two different segments i.e. traditionalists and modernists and a crucial difference of opinion lies regarding woman as head of Islamic state between the two. On one side, Syed Maududi, Amin Ahsan Islahi, and Syed Jalal ud Din Umri, are highly reluctant regarding women’s position as head of Islamic state and other political activities. Resultantly, they face bitter criticism of modern and secular Muslims alike. On the other side, Rehmatullah Tariq, Rafiullah Shahab and Asghar Ali Engineer claim that women have ample political rights in this respect as Islam does not inhibit them from assuming public office. The present paper intends to discuss the women leadership as head of Islamic state in view of Islamists, modernists. An attempt is also made to know the real intention of Sharīʿah regarding the role of women as head of Islamic state and its limitations ordained by Islam. A reference of feminist scholars is also made to know their point of view on the issue.